Kearifan Lokal dalam Novel Mata dan Manusia Laut Karya Okky Madasari dan Pemanfaatanya sebagai Bahan Ajar di SMA - Sofinah Rania Al Yassin; Imam Muhtarom; Dewi Herlina Sugiarti (Peneliti.net, 2021)
This study aims to describe the value of local wisdom contained in the novel Mata and Man Laut by Okky Madasari. The type of research used is qualitative research with library techniques. The subject of this research is the novel Mata and Laut Man. Data collection uses content analysis techniques by reading and taking notes. The results of this study indicate that the novel Mata and Man Laut contains the values ​​of local wisdom. So that this research is in accordance with the objectives of education in Indonesia regarding the introduction of cultural diversity and Indonesian society.